2019
DOI: 10.1002/mame.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of PMMA‐Sepiolite Nanocellular Materials with a Bimodal Cellular Structure

Abstract: Bimodal cellular poly(methyl methacrylate) with micro‐ and nano‐sized (300–500 nm) cells with up to 5 wt% of sepiolite nanoparticles and porosity from 50% to 75% are produced by solid‐state foaming. Uniaxial compression tests are performed to measure the effect of sepiolite concentration on the elastic modulus and the yield strength of the solid and cellular nanocomposites. Single edge notch bend tests are conducted to relate the fracture toughness of the solid and cellular nanocomposites to sepiolite concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
1
18
0
1
Order By: Relevance
“…Microstructural parameters such as the average cell size l, standard deviation s of the observed cell sizes, and cell nucleation density N d , using the method as suggested by Kumar & Suh [27], were obtained. 13…”
Section: (Ii) Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural parameters such as the average cell size l, standard deviation s of the observed cell sizes, and cell nucleation density N d , using the method as suggested by Kumar & Suh [27], were obtained. 13…”
Section: (Ii) Microstructurementioning
confidence: 99%
“…The available data on the cell size and porosity that have been achieved to date for high porosity (PMMA-based) polymeric nanofoams via solid-state foaming are summarized in figure 1. Data are retrieved from [4,[9][10][11][12][13][14][15][16][17]. It is clear that the ideal combination of high porosity ( f > 0.85) and small cell size (l < 200 nm) is yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The measured values of E, σ y , and K Ic for each foamed sample made from a given PMMA grade were normalised with respect to the values for E, σ y , and K Ic of the solid materials of the same grade: I c , s are the properties of the solid PMMA. Note that data from a previous work [15] are examined in this section too in order to extend the relative density range of the microcellular PMMA; the microcellular PMMA materials considered in this work have an average cell size ranging from 3.2 μm to 4.3 μm and relative density ranging from 0.29 to 0.52.…”
Section: Mechanical Properties Of the Pmma Foamsmentioning
confidence: 99%
“…Guo [14] conducted uniaxial tensile tests on polycarbonate (PC) nanocellular and microcellular foams and demonstrated that the Young's modulus and tensile ductility are independent of cell size, whereas the yield strength increases with diminishing cell size for a fixed value of relative density. Bernardo et al [15] found that the Young's modulus, yield strength and fracture toughness of nanocellular composites made from PMMA and sepiolite particles were dependent upon the concentration and the dispersion of the particles, but independent of cell size.…”
Section: Introductionmentioning
confidence: 99%